Impaired Cerebral Hemodynamics and Cognitive Performance in Patients with Atherothrombotic Disease - Haratz, Salo (J Alzheimers Dis, 2015)
BACKGROUND AND OBJECTIVE: Patients with pre-existing atherothrombotic disease are prone to cognitive impairment. We tested whether impaired cerebrovascular reactivity (CVR), a marker of cerebral microvascular hemodynamic dysfunction, is associated with poorer cognitive scores among patients with and without carotid large-vessel disease. METHODS: A subgroup of non-demented patients with chronic coronary heart disease followed-up for 15 ± 3 years was assessed for cognitive function (Neurotrax Computerized Cognitive Battery; scaled to an IQ style scale with a mean of 100 and SD of 15) and for CVR using the breath-holding index (BHI) with transcranial Doppler and for carotid plaques using ultrasound. We assessed cognitive scores in specific domains in patients with and without impaired CVR (BHI <0.47; bottom quartile). RESULTS: Among 415 patients (mean age 71.7 ± 6.2 y) median BHI was 0.73 (25% 0.47, 75% 1.04). Impaired CVR was associated with diabetes and peripheral artery disease. Adjusting for potential confounders, impaired CVR was associated with lower executive function (p = 0.02) and global cognitive scores (p = 0.04). There was an interaction with carotid large-vessel disease for executive function (p < 0.001), memory (p = 0.03), and global cognitive scores (p = 0.02). In the carotid large-vessel disease group there were pronounced differences by CVR status in executive function (p < 0.001), memory (p = 0.02), attention (p < 0.001), and global cognitive scores (p = 0.001). CONCLUSION: Impaired CVR, a marker of cerebral microvascular dysfunction, is associated with poorer cognitive functions and in particular executive dysfunction among non-demented patients with concomitant carotid large-vessel disease. These findings emphasize the importance of cerebral hemodynamics in cognitive performance.